Answer:
5×(-4) = -20
(-1) × 4 = -4
Explanation:
Here it' sayin when a positive number ( it may be odd or even ) gets multiplied with an even number ( it may be positive or negative ) , the product will be positive number.
5×(-4) = -20 .Here 5 is a positive number & 4 is a negative even number but the product -20 is a negative number. So it contradicts the statement.
(-1) × 4 = -4 . Here -1 is a negative number & 4 is a positive even number but the product -4 is a negative number. So it contradicts the statement.